Diversity of Vascular Niches in Bones and Joints During Homeostasis, Ageing, and Diseases - Kumar, Naveen; Saraber, Pepijn; Ding, Zhangfan; Kusumbe, Anjali P. (Frontiers in Immunology, 2021)
Skeleton is composed of diverse cell types, including bone cells, connective tissue cells and mineral deposits and regulate whole-body homeostasis. The capacity of maintaining strength and generation of blood lineages lies within the skeletal system. Bone harbours blood and immune cells and their progenitors, and vascular cells provide several immune cell types niches. Blood vessels in bone are phenotypically and functionally diverse, with distinct capillary subtypes exhibiting striking changes with age. The bone vasculature has a special impact on osteogenesis and haematopoiesis, and dysregulation of vasculature is associated with diverse blood and bone diseases. Ageing is associated with perturbed haematopoiesis, loss of osteogenesis, increased adipogenesis and diminished immune response and immune cell production. Endothelial and perivascular cells impact immune cell production and play a crucial role during inflammation. Here, we discuss normal and maladapted vascular niches in bone during development, homeostasis, ageing and bone diseases such as rheumatoid arthritis and osteoarthritis. Further, we discuss the role of vascular niches during bone malignancy.